A computational study of soot formation and flame structure of coflow laminar methane/air diffusion flames under microgravity and normal gravity. Issue 5 (3rd September 2017) - Veshkini, Armin; Dworkin, Seth B.
Abstract : A numerical study is conducted of methane–air coflow diffusion flames at microgravity (μ g ) and normal gravity (1 g ), and comparisons are made with experimental data in the literature. The model employed uses a detailed gas phase chemical kinetic mechanism that includes PAH formation and growth, and is coupled to a sectional soot particle dynamics model. The model is able to accurately predict the trends observed experimentally with reduction of gravity without any tuning of the model for different flames. The microgravity sooting flames were found to have lower temperatures and higher volume fraction than their normal gravity counterparts. In the absence of gravity, the flame radii increase due to elimination of buoyance forces and reduction of flow velocity, which is consistent with experimental observations. Soot formation along the wings is seen to be surface growth dominated, while PAH condensation plays a more major role on centreline soot formation. Surface growth and PAH growth increase in microgravity primarily due to increases in the residence time inside the flame. The rate of increase of surface growth is more significant compared to PAH growth, which causes soot distribution to shift from the centreline of the flame to the wings in microgravity.